Development of Word Wall Game Media for Fiqh E-Learning Through a Blended Cooperative Learning Model - Hartan, Win; Khodijah, Nyayu; Wigati, Indah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This research aims to develop a Word Wall Game learning media based on Blended Cooperative E-Learning for fiqh education. The research method employed is Research and Development (R&D). The study involved a diverse group of participants, including experts (media experts, learning experts, and fiqh teachers) and grade VIII students, with a total of 210 participants. The sample was selected using a simple random sampling technique, involving 8 validators from experts and teachers, as well as 40 students for a small-scale trial and 30 students for a large-scale trial based on Roscoe's theory. Data were collected through questionnaires, interviews, and tests and analyzed using qualitative and quantitative descriptive methods. The results indicate that the Word Wall Game media is valid for use in fiqh learning. Validation scores from media design experts reached 81.66% (valid category), learning experts scored 91.66% (very valid), and fiqh teachers provided a score of 88.33% (valid), with recommendations for improving contextual elements of fiqh content. The media was found to be effective in terms of appearance, materials, and methods. In terms of practicality, it was rated as easy to use by students, with an average practicality score of 4.16. Furthermore, the media significantly enhanced student motivation and engagement in learning, particularly on the topic of halal and haram food and beverages. The effectiveness of the media was demonstrated through improved student comprehension, as measured by the N-Gain Score method. The average N-Gain score of 0.65 and 0.67 indicates a medium improvement in student understanding. In conclusion, the Word Wall Game media based on Blended Cooperative E-Learning has been validated as a practical and effective tool for enhancing fiqh learning. This media demonstrates potential for broader application and further refinement to optimize student learning outcomes.